Layout Planning of Finished Goods Warehouse Using Class-Based Storage Method Based on Turnover Ratio in PT XYZ: Perencanaan Tata Letak Gudang Barang Jadi Menggunakan Metode Class-Based Storage Berdasarkan Turnover Ratio di PT XYZ - Erliansa Fatmawati; Nur Rahmawati (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2025)
The increasing demand in the agricultural and manufacturing sectors, especially for fertilizers and dolomite mining materials, has driven the need to optimize the management of finished goods warehouses. The current goods management system in PT XYZ's warehouse is not yet effective and efficient, including the storage of goods is not yet organized and not well organized, resulting in several impacts that affect the decline in warehouse performance. This study aims to provide a proposal for warehouse layout planning at PT XYZ using the class-based storage method combined with FSN (Fast, Slow, Non-Moving) analysis based on the turnover ratio (TOR) by grouping goods according to the turnover rate so as to maximize the utilization of warehouse space, speed up the process of picking goods, and increase operational efficiency. The results of the re-planning show that the capacity of Warehouse 1 decreased by 4.6% or 721 tons and Warehouse 2 by 19.4% or 2,043 tons, by allocating part of the area for transportation maneuver lines and defective goods processing areas, sieving machines, screen printing areas, and auxiliary material storage areas. Product grouping resulted in 11 types of products in the fast-moving category, 1 type in the slow-moving category, and 2 types in the non-moving category. The proposed new warehouse layout has proven effective in shortening material handling distances, accelerating the goods transportation process, and supporting smooth distribution of goods.